2015
DOI: 10.1186/s12885-015-1726-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between apparent diffusion coefficients and HER2 status in gastric cancers: pilot study

Abstract: BackgroundTo evaluate whether apparent diffusion coefficient (ADC) value of gastric cancer obtained from diffusion weighted imaging (DWI) correlates with the HER2 status.MethodsForty-five patients, who had been diagnosed with gastric cancer through biopsy, were enrolled in this IRB-approved study. Each patient underwent a DWI (b values: 0 and 1,000 sec/mm2) prior to surgery (curative gastrectomy or palliative resection). Postoperative microscopic findings, HER2 status by immunohistochemical analysis and fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
2
18
1
Order By: Relevance
“…DW‐MRI can provide information on the microscopic structure of tissue by measuring the diffusion of water molecules within tissue . ADC, derived from DW‐MRI, has been used as an imaging biomarker to predict the histopathologic grade, therapeutic response and prognosis of some tumors, including PCa . Based on the clinical utility of tumor biomarkers and ADC in PCa, the current study was designed to examine the association between ADC and pathological parameters and tumor biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DW‐MRI can provide information on the microscopic structure of tissue by measuring the diffusion of water molecules within tissue . ADC, derived from DW‐MRI, has been used as an imaging biomarker to predict the histopathologic grade, therapeutic response and prognosis of some tumors, including PCa . Based on the clinical utility of tumor biomarkers and ADC in PCa, the current study was designed to examine the association between ADC and pathological parameters and tumor biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) can be derived from DW‐MRI, which provides a method to quantitatively analyze the water diffusion in tissue. Previous studies have used ADC as an imaging biomarker to predict the histopathological grade, therapeutic response and prognosis of some tumors, including PCa . However, few studies have concentrated on the association between ADC and these biomarkers in PCa.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid progress in imaging techniques, magnetic resonance imaging (MRI) has been used more frequently in the preoperative evaluation of gastric cancers owing to its superior soft‐tissue contrast compared to computed tomography (CT) . Especially diffusion‐weighted imaging (DWI), which could reflect the microstructures of tissues in vivo, has been shown to be useful in detecting, differentiating, and characterizing gastric cancers noninvasively based on multiple previous studies …”
mentioning
confidence: 99%
“…In quantitative terms, the apparent diffusion coefficient (ADC) values could help differentiate between gastric cancers and normal gastric mucosa as well as between gastric adenocarcinoma and lymphoma . Previous studies have also shown that the ADC values may be helpful as a noninvasive tool for evaluating the histological features, HER‐2 status, and TNM staging of gastric cancer . However, the ADC values of most previous studies were obtained from a region of interest (ROI) that was manually drawn on one slice of the lesion, resulting in possible measurement sampling error and subjective bias.…”
mentioning
confidence: 99%
“…16 Previous studies have also shown that the ADC values may be helpful as a noninvasive tool for evaluating the histological features, HER-2 status, and TNM staging of gastric cancer. 7,8,17 However, the ADC values of most previous studies were obtained from a region of interest (ROI) that was manually drawn on one slice of the lesion, resulting in possible measurement sampling error and subjective bias. Moreover, the mean ADC value was the only parameter obtained, which does not reflect the heterogeneity of the entire lesion.…”
mentioning
confidence: 99%